East option of a relativism in a context of game model (Journal of Philosophy Culture and Political Science, 2019)
In this article the author defi nes east version of relativism in a context of game model. According to author's idea, east version of relativism differs with aspiration to semantic games, hints, unexpected connection of various semantic elements, combinations, interpretations and comments. Important line of east version of relativism is strategy of roundabout maneuver. Keywords: game, phenomenon of culture, model of culture, relativism, playing thinking, way of thinking.